The Halt of the Constitucional Process and the Consequences of the Potencial Non-Enforcement - Vida, KRISZTINA (Papeles del Este, 2006)
The article makes an inventory of the major innovations of the Constitucional Treaty and attempts to analyse what EU citizens lose with the potential nonratification of the document. The outcome of the analysis is that EU citizens lose a more streamlined and transparent system of primary law enriched with important constitutional values (including the protection of minority rights), they lose an improved institutional balance and increased democratic input, as well as the reinforcement of the policies aiming at higher internal security and stronger external action. The rest of the policies will remain unchanged as the Constitutional Treaty did not substantially reform them. What citizens might win from the two negative referenda, however, is the high probability of the EU institutions’ introducing more transparency and democracy into their daily functioning, coupled with the preparedness of both the institutions and the Member States to engage in a real dialogue with the wide public on the future of the European Union.